The frequency of detection of various forms of deforming bronchitis during endoscopic examination of patients with bleeding from the broncho-pulmonary system - Makarova, G. V.; Avramenko, A. A. (Journal of Education, Health and Sport, 2018)
237 patients were examined with bleeding from the broncho-pulmonary system. During the bronchoscopy, it was revealed that all patients suffered from deforming bronchitis of various forms: 73 (30.8%) patients had atrophic bronchitis, a primary inflammatory form; in 111 (46.8%) patients - primary dystrophic form of atrophic bronchitis; in 53 patients (22.4%) - diffuse, bilateral bronchitis of II and III degree of inflammation intensity. 237 patients were examined with bleeding from the broncho-pulmonary system. During the bronchoscopy, it was revealed that all patients suffered from deforming bronchitis of various forms: 73 (30.8%) patients had atrophic bronchitis, a primary inflammatory form; in 111 (46.8%) patients - primary dystrophic form of atrophic bronchitis; in 53 patients (22.4%) - diffuse, bilateral bronchitis of II and III degree of inflammation intensity.